AKUT AKCİĞER HASARINDA İNTRATRAKEAL DEKSAMETAZONUN LİPİD PEROKSİDASYONUNA ETKİLERİ - MEYANCI, Güniz; ARICIOĞLU, Funda; ÖZ, Hüseyin; AYDEMİR, Akın (Cerrahpaşa Medical Journal, 2019)
Background and Design.- The aim of our study was to show the effect of intratracheal (IT) dexamethasone on lipid peroxidation in hydrochloric acid (HCl) aspiration induced acute lung injury of rabbits. We measured the levels of malonyldialdehyde (MDA) which is end product of lipid peroxidation in plasma and bronchoalveolar lavage (BAL). Fourteen New Zeland rabbits were randomly assigned to 2 groups as the control group (CG, n=6) and dexamethasone group (DG, n=8). An endotracheal tube was placed trough a tracheostomy in all animals following ketamine hydrochloride (50 mg/kg, intramusculary) induced anesthesia. Maintenance of anesthesia was achived by the use of ketamine hydrochloride 10 mg/kg/h and atracurium besylate 1mg/kg/h. The animals were ventilated with pressure control mode for 5 hours and the parametres of ventilation were FiO2: 1.0, RR: 80/min, VT: 10 mL/kg, PEEP: 5 cmH2O. IT HCl (2mL/kg) was given following the initial sampling of MDA from plasma and BAL. Five minutes after the application of HCl the DG received IT dexamethasone (2.5mg/kg). Plasma and BAL resampling for the measurement of MDA was done at the second and fifth hour of HCl aspiration. Results.- The levels of MDA in the fifth hour samples of plasma and BAL were significantly different between two groups (p<0.01). (Mean plasma MDA levels of DG and CG were 1.14±0.6 nmol/mL and 2.5±1.36 nmol/mL, respectively; mean BAL MDA levels of DG and CG were 1.03±0.3 nmol/mL and 3.18±1.2 nmol/mL, respectively). Conclusion.- Intratracheal dexamethasone given after 5 minutes of HCl aspiration had a beneficial effect on the lipid peroxidation in acute lung injury of rabbits.